What data privacy problems does users face in the big data environment? - Zhang, Xiaotong (2019)
With the rapid development of big data and cloud computing, people's life has been greatly improved. At the same time of obtaining convenient life experience, the information generated by users' daily life may be recorded, stored, analyzed and applied. Although the age of big data has brought convenience to people's life and work, a bigger problem -- privacy leakage is becoming more and more serious. In order to find out the problems of user information privacy leakage in the big data environment, this paper firstly analyzes the characteristics and main applications of current big data technology and cloud computing technology, and points out the existing problems of user information privacy in both technology and users. Then it studies the typical cases of applying big data and cloud computing, and finally analyzes the specific ways that may lead to the disclosure of user information privacy through the practical application of big data and cloud computing.